CSS for designers : organizing, developing, and optimizing your CSS (O'Reilly Media, 2015)
"CSS is a powerful language for creating and controlling your website's presentation, but it's more of a visual language than a traditional coding tool. With this video workshop, you'll quickly learn how to solve a wide range of style issues with CSS, whether you're a web designer just starting to code, an experienced developer looking to refresh your skills, or a student looking to get into web design. UX designer Adrian Mendoza starts with the basics and then adds layers of code and complexity as the course progresses. Along the way, you'll learn how to create a non-functional spec, build a style guide, and develop page templates."--Resource description page.